Earnings Management, Debt Maturity, Dividend Policy and Future Performance of Manufacturing Companies in Indonesia - Filiana Filiana; Bandi Bandi (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to examine the relationship between earnings management, debt maturity, and dividend policy on the future performance of manufacturing companies in the capital market in Indonesia. This study uses manufacturing companies listed on the Indonesian stock exchange in the period 2014 to 2019. Sampling in this study uses a purposive sampling technique. The data analysis method in this study is multiple regression analysis using 192 observational data. The results of this study find that simultaneously earnings management, debt maturity and dividend policy have a significant effect on the company's future performance. Partially, earnings management variables have a negative effect on the company's future performance, and the debt maturity variable has a positive effect on the company's future performance. The dividend policy variable partially has no effect on the company's future performance.